Role of Motivation in Employee Retention: A Study on Readymade Garments Manufacturing Company in Bangladesh (Global Journal of Management and Business Research, 2023)
The objective of this research is to assess the influence of motivation on employee retention within the Readymade garments sector of Bangladesh During the study a customized questionnaire was formulated to conduct a survey A total of 72 participants from various garments companies were surveyed The research utilized statistical techniques including reliability analysis validity analysis correlation and regression analysis to scrutinize the collected survey data The analysis was performed using statistical software SPSS version -20 The results of the study indicate that factors contributing to motivation such as compensation work-life-balance job environment supervisor-subordinate relationships attractive salary and wages supervision working hours and both extrinsic and intrinsic benefits exert a substantial impact on the ability to retain employees within Bangladesh s Readymade Garments Industry
Keywords: work-life-balance; superior-subordinate relationships; attractive salary and wages; extrinsic and intrinsic motivational benefits